Studi Analisi Pola Komunikasi Interpersonal dalam Film Surga yang tak Dirindukan Karya Kunts Agus Tahun 2015 - Khoirul Muslimin; Lailiyatuzzahroh Al Jannah (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2018)
Impersonal communication is the most basic thing. Through the good impersonal communication, the relationship that tied in is good too. In “Surga yang Tak Dirindukan” movie, there are some scene that describe impersonal communication among the actors. Besides as the place of impersonal communication, “Surga yang Tak Dirindukan” contains the preaching contents that can be use for faundation of attitude and standing. The movie was released on July 2015 that directed by Kuntz Agus. The purpose of the research is to know how the pattern of impersonal communication in “Surga yang Tak Dirindukan” movie, and search the preaching contents that contained in it. The kind of the research is descriptive qualitative and semiotic data analysis of Roland Barthes type. The result of the research is the communication that used among the actors of “Surga yang Tak Dirindukan” movie. It is diadic communication (communication between two people), that happen on primer and secunder. But sometimes also use triadic communication (communication among three people). Some preaching contents that contained in it are helping someone who needs, being a good leader, being a loyal wife, being a good sincer kind mother and sincerity to yield.